2003
DOI: 10.1038/sj.ijo.0802289
|View full text |Cite
|
Sign up to set email alerts
|

The postprandial response of adiponectin to a high-fat meal in normal and insulin-resistant subjects

Abstract: OBJECTIVE:Adiponectin is an adipose-specific protein with short-term effects in vivo on glucose and fatty acid levels. We studied the plasma concentration and the proteolytic activation status of adiponectin following the consumption of a high-fat, lowcarbohydrate meal. DESIGN: Analysis of adiponectin concentration and polypeptide structure after consumption of a fat meal. SUBJECTS: Normal subjects (n ¼ 24) and first-degree relatives of patients with type II diabetes (n ¼ 20). MEASUREMENTS: All subjects had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
63
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 17 publications
17
63
3
2
Order By: Relevance
“…Moreover, we found no effect of either test meal on plasma adiponectin. This agrees with some previous studies on the impact of fat on plasma adiponectin in insulin-sensitive and insulin-resistant individuals [36]. Whereas, in the majority of studies, plasma adiponectin decreased in response to a high-fat meal [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we found no effect of either test meal on plasma adiponectin. This agrees with some previous studies on the impact of fat on plasma adiponectin in insulin-sensitive and insulin-resistant individuals [36]. Whereas, in the majority of studies, plasma adiponectin decreased in response to a high-fat meal [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…Postprandial values of triglyceride, insulin, non-esterified fatty acid and triglyceride were similar in the relatives of patients with diabetes and control subjects, and to those in similar studies using the same fat meal (15,16). Glucose levels were essentially unchanged, and there was no significant difference (, 5%) between the proportions of each adiponectin isomer present in basal and postprandial samples.…”
Section: Postprandial Response To a High Fat Mealsupporting
confidence: 68%
“…The protocols used to characterise the subjects and administer a fat meal and an oral glucose tolerance test have been reported previously in a study on a similar group of subjects (15,16). Body composition was assessed by dual energy emission x-ray absorptiometry (DEXA) and whole-body insulin sensitivity by a 120-min euglycaemic, hyperinsulinaemic clamp.…”
Section: Subjectsmentioning
confidence: 99%
“…Peake et al 26 found no difference in adiponectin response to a mixed meal between normal and insulinresistant subjects over a 6-hour period; however, basal adiponectin values were similar in the two groups, and the mixed meal elicited a significant insulin rise. 26 Vuppalanchi et al 27 found no difference in adiponectin response to a mixed meal between NASH patients and controls after 3 hours. It is possible that the abundance of adiponectin in blood, as compared with any other adipokines, and its long half-life (2.5-6 hours) may have masked any acute regulatory action of lipid load over the short term in previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…The absence of carbohydrate in the test meal was designed to prevent the significant postprandial glucose and insulin increase elicited by mixed meals used in other studies. [26][27][28] The ability of insulin to suppress human adiponectin gene expression 29 and the release of FFA and to enhance triglyceride catabolism may in fact affect postprandial lipid and adiponectin responses. 30 The higher postprandial lipid response observed in our patients could play a role in liver Tg accumulation, as the magnitude of FFA increase correlated significantly with the severity of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%